Theoretical and methodological prerequisites for the application of multimedia teaching materials in professional preparing for a future music teacher (Pedagogy of Higher and Secondary Education, 2009)
The article considers the possibilities of using multimedia teaching aids in terms of taking into account the peculiarities of scientific and artistic creativity.
Keywords: music teacher; multimedia technologies; computer technologies; reference; integration of auditory and visual components